2021
DOI: 10.1016/j.jmig.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Association of Race/Ethnicity with Surgical Route and Perioperative Outcomes of Hysterectomy for Leiomyomas

Abstract: To evaluate the associations among race/ethnicity, route of surgery, and perioperative outcomes for women undergoing hysterectomy for uterine leiomyomas. Design: Retrospective cohort study. Setting: Multistate. Patients: Women who underwent hysterectomies for leiomyomas from the American College of Surgeons National Surgical Quality Improvement Program database, 2014 to 2017. Interventions: None. Exposures of interest were race/ethnicity and route of surgery. Measurements and Main Results: Racial/ethnic variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
0
22
0
1
Order By: Relevance
“…Of these, 81 studies were subsequently excluded after the examination of the abstract and full text: 29 manuscripts were excluded because only the abstract was retrieved, 24 as they did not have English language and 28 because they did not have an adequate population and intervention. Definitively, 38 articles were included in our systematic review ( Figure 1 ) [ 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Data synthesis was available in Table 1 and Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 81 studies were subsequently excluded after the examination of the abstract and full text: 29 manuscripts were excluded because only the abstract was retrieved, 24 as they did not have English language and 28 because they did not have an adequate population and intervention. Definitively, 38 articles were included in our systematic review ( Figure 1 ) [ 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Data synthesis was available in Table 1 and Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The most common therapy for cervical leiomyomas is represented by surgery; however, compared to myomas of the uterine corpus, which are treated with conservative myomectomy [ 10 , 11 ] or hysterectomy [ 12 ], the surgical treatment of cervical leiomyomas can be more difficult; this is due to the risk of intraoperative hemorrhage and to the potential injuries to the adjacent organs that are often dislocated and contiguous to the cervical leiomyoma; this may cause a subverted anatomy of the pelvis requiring experienced surgeons [ 13 ]; furthermore, the position of the leiomyoma in the cervix poses an extra challenge in the surgical approach in case of a fertility-sparing approach. Currently, a standard surgical treatment for the leiomyomas of the cervix still lacks; therefore, the therapeutic approach depends on the characteristics of the patient, the desire for fertility and the experience of the individual centers and surgeons [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…When considering patient demographics, Black and other minorities have poorer surgical outcomes and undergo fewer minimally invasive surgical procedures. 3 Researchers have hypothesized that the discrepancy in fibroids, uterus size, socioeconomic status, medical comorbidities, and medical access may explain the disparity in MIHs. 3 However, recent studies have revealed that even when accounting for these factors, Black women experience more postoperative complications.…”
Section: Route Of Surgerymentioning
confidence: 99%
“…3 Researchers have hypothesized that the discrepancy in fibroids, uterus size, socioeconomic status, medical comorbidities, and medical access may explain the disparity in MIHs. 3 However, recent studies have revealed that even when accounting for these factors, Black women experience more postoperative complications. Ko and colleagues, in a study of 20,133 women undergoing hysterectomy, described significant differences in surgical route by race.…”
Section: Route Of Surgerymentioning
confidence: 99%
See 1 more Smart Citation